Peningkatan Hasil Belajar Mengunakan Model Discovery Learning Berbasis TPACK Pada Pembelajaran IPAS Kelas V Sekolah Dasar - Putri Khairani; Arwin Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
The background of this research stems from the issue of low student academic achievement, which is primarily caused by a teacher-centered learning approach. This condition results in students being less actively engaged and unable to independently comprehend the subject matter. To address this issue, the study aims to describe efforts to improve IPAS learning outcomes through the implementation of the Discovery Learning model integrated with the TPACK framework for fifth-grade students at SDN 24 Parupuk Tabing in Padang City. The method employed is Classroom Action Research (CAR), using a combination of qualitative and quantitative approaches conducted in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The research involved 20 students and one teacher, with data collected through both tests and observations. The findings show significant improvements: the quality of instructional modules increased from 90,625% to 96,87%, teacher performance improved from 89,06% to 96,87%, student engagement rose from 89,06% to 96,87%, and the average student score increased from 81,41 to 90,5 In conclusion, the Discovery Learning model based on the TPACK approach is proven to effectively enhance students' learning outcomes in IPAS.